The Climate Action Plan of the city of Teresina, PI and the case of the Vila da Paz neighborhood: perpetuating inequalities in vulnerable urban territories - Mendes, Élgen Soares; Toledo , Renata Ferraz de (Technical and Scientific Journal Green Cities, 2025)
Objective – to analyze the Vila da Paz Urbanization Project from the perspective of creating adaptive capacities and climate resilience. Methodology – qualitative case study, supported by bibliographical and documentary research and field surveys. Originality/Relevance – bring science, politics, and society closer together, and raise awareness among public policymakers about the urgency of taking action to to address the possibility of these policies promoting climate injustices. Results – The Vila da Paz Urbanization Project did not promote the creation of adaptive capacities and climate resilience; on the contrary, it created new vulnerabilities and increased some of the existing ones. Theoretical/Methodological Contributions – highlights the importance of studies that critically analyze public policies and their implications in vulnerable urban areas. Social and Environmental Contributions – highlights the importance of social participation and intersectionality studies in the development of public climate policies.